Some statistical investigations on the nature and dynamics of electricity prices - Giulio Bottazzi; Sandro Sapio; Angelo Secchi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2004)
It is widely accepted that in liberalized electricity markets log-returns display fat-tailed densities. Besides qualitative assessments, so far precise characterizations of the shape of the distribution have been seldom provided. In this work, we characterize the conditional and unconditional probability density functions of daily electricity log-returns, and of the underlying shocks from the NordPool market, for each of the 24 hours, through a very flexible and general family of distributions, namely the Subbotin family. Our study contributes with novel results in the field. First, we show that price fluctuations in electricity markets are additive in nature. We do this by exploiting a scaling relationship between price level and volatility, which is in turn a new result in the electricity markets literature. Second, in line with recent studies, we uncover the existence of multiple regimes in price dynamics, and we characterize the distributional shape for each of them. Interestingly, the shocks behind electricity price dynamics are approximately Laplace if one conditions on low price levels, and closer to a Gaussian in correspondence of high initial price levels. These results are at variance with the evidence from financial markets. The peculiar non-storable nature of electricity, and the varying strength of correlations between bidding behaviors at different load levels are suggested as possible key factors behind the specificities of electricity markets outcomes.
Keywords: C16; D4; L94; 330; Electricity Markets; Subbotin Distribution; Laplace Distribution; Additive Process; Scaling; Strompreis; Elektrizitätswirtschaft; Deregulierung; Nordeuropa; Statistische Verteilung